Epilepsy Combined With Multiple Gene Heterozygous Mutation - Qiuju, He; Jianlong, Zhuang; Qi, Wen; Zhifa, Li; Ding, Wang; Xiaofang, Sun; Yingjun, Xie (Frontiers in Pediatrics, 2022)
The fast pace of gene discovery has resulted in groundbreaking advances in the field of epilepsy genetics. Clinical testing using comprehensive gene panels, exomes, or genomes is now increasingly available and has significantly increased the diagnostic yield for early-onset epilepsies and enabled precision medicine approaches. In this paper, we report a case of epilepsy in a pedigree. The proband had heterozygous mutations in KCNC1 (NM_001112741.1:c.959G>A, p. Arg320His), CAPN3 (NM_000070.2:c.526G>A, p. Val176Met), and NEFH (NM_021076.3:c. 2595 delC, p. Lys866Argfs*51). Sanger sequencing verification was consistent with the results of whole exome sequencing. The KCNC1 mutation was a de novo mutation, and the CAPN3, and NEFH mutations were inherited from their father and mother, respectively. Based on the American College of Medical Genetics and Genomics (ACMG) guidelines, a heterozygous mutation was found for APOB (NM_000384.2: c.10579C > T, p. Arg3527Trp). The heterozygous mutation at this site was inherent in the pedigree. Coexpression analysis indicated that heterozygous mutations of KCNC1, CAPN3, NEFH and APOB were closely related to the clinical phenotypes of the patient, and the clinical phenotypic heterogeneity of the disease was the result of the interaction of multiple genes.